COMPARISON OF GLOBAL MEAN TEMPERATURE SERIES STRATEGIES FOR BEGINERS - Thomson, Pro. Screw; Millar, Dr. Methew Millar (International Journal of Multidisciplinary Research and Studies, 2021)
This paper discusses general aspects of smart grids and focuses on some smart grid features at distribution levels like interconnection of distributed generation and active distribution management, using automated meter reading (AMR) systems in network management and power quality monitoring, application of power electronics in electricity distribution, plug-in vehicles as a part of smart grids, and frequency-based load control as samples of interactive customer gateway